2018
DOI: 10.31326/jks.v1i02.143
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Adaptation Costs of Climate Change: Case Study of Indramayu, West Java Indonesia

Abstract: ECONOMIC AND ADAPTATION COSTS OF CLIMATE CHANGE: CASE STUDY OF INDRAMAYU, WEST JAVA INDONESIA Abstract Climate change is already occurring. In Indonesia, many evidences such as changing rainfall patterns in many parts of the country (e.g., Sumatra and Java) indicate the impacts of global climate change on Indonesian climate. This new climate regime eventually will influence water availability in many parts of the country. This paper discusses economic loss (unit cost) incurred on major economic sectors (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…With a land area of 2,099.42 km 2 and 147 km coastline (Statistics-Indonesia 2020a), the Indramayu district is one of ten areas on Java's North coast prone to Rob and inundation hazards. Rob flooding occurs annually in July and August and can inundate fishponds over 15 days (Perdinan et al 2014). By 2030 the district is to experience the province' second-largest coastal inundation, affecting 10,000 ha of fishponds (Suroso and Firman 2018).…”
Section: Methodsmentioning
confidence: 99%
“…With a land area of 2,099.42 km 2 and 147 km coastline (Statistics-Indonesia 2020a), the Indramayu district is one of ten areas on Java's North coast prone to Rob and inundation hazards. Rob flooding occurs annually in July and August and can inundate fishponds over 15 days (Perdinan et al 2014). By 2030 the district is to experience the province' second-largest coastal inundation, affecting 10,000 ha of fishponds (Suroso and Firman 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Prihantini [242] reported that the total economic losses affected by the flood in Dalpinang District, Madura Island were over IDR 5.8 billion. In Indramayu District, the flood caused an economic loss of about IDR 744 million [243]. From 2014 to 2019, it was estimated that the average economic loss due to flooding in North Aceh Regency was approximately IDR 675.35 billion [244].…”
Section: Threats and Challenges Of Climate Change On The Economic Asp...mentioning
confidence: 99%